The Effectiveness of Cherry (Muntingia calabura L) leaves extract on gourami (Osphronemus goramy) seeds infected with the bacteria Aeromonas hydrophila - Mellisa Siska; Rahman Putra Ihsan (BIO Web of Conferences)
Gourami (Osphronemus goramy), a high-value fish, faces challenges in growth and survival due to bacterial infections, particularly Aeromonas hydrophila. This study analyzed the effects of cherry (Muntingia calabura) leaves extract at different doses on gourami infected with A. hydrophila. A completely randomized design (CRD) with five treatments and three repetitions was used: Treatment A (negative control), Treatment B (positive control), and Treatments C, D, and E (fish challenged with A. hydrophila and immersed in 50 ppm, 70 ppm, and 90 ppm of cherry leaves extract, respectively). Results showed that cherry leaves extract significantly improved fish survival and health. Treatment C (50 ppm) yielded the best outcomes, with 76.66% survival, leucocyte counts of 165.3 x 10³ cells/mm³, and hemoglobin levels of 8 g/dL. It also reduced mucus production, healed ulcers, and stabilized blood parameters. Thus, 50 ppm cherry leaves extract was the most effective dose for enhancing gourami health and survival against A. hydrophila infections.